The Effect of the Severity of Preoperative Leg Pain on Patient-Reported Outcomes, Minimum Clinically Important Difference Achievement, and Patient Satisfaction After Minimally Invasive Transforaminal Lumbar Interbody Fusion - Jacob, Kevin C.; Patel, Madhav R.; Collins, Andrew P.; Parsons, Alexander W.; Prabhu, Michael C.; Vanjani, Nisheka N.; Pawlowski, Hanna; Singh, Kern (World neurosurgery, 2022)
To compare patient-reported outcome measures (PROMs), satisfaction, and minimum clinically important difference (MCID) achievement after minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) in patients stratified by preoperative leg pain. Patients undergoing MIS-TLIF were collected through retrospective review of a prospectively maintained single-surgeon database. PROMs administered preoperatively/postoperatively included Patient-Reported Outcomes Measurement Information System Physical Function (PROMIS-PF), visual analog scale (VAS) back/leg pain, Oswestry Disability Index (ODI), and 12-Item Short Form (SF-12) Physical/Mental Component Score (PCS/MCS). Patients were grouped based on preoperative VAS leg scores: VAS leg ≤7 or VAS leg >7. Inferential statistics were used to compare PROMs, MCID achievement rates, and postoperative satisfaction between groups. A total of 562 patients were eligible (168 VAS leg score ≤7; 394 VAS leg score >7). Significant differences between cohorts in postoperative mean PROMs were noted for PROMIS-PF at 6 weeks/2 years, SF-12 PCS at 6 weeks/2 years, SF-12 MCS at 6 weeks/12 weeks/6 months/1 year, VAS back score at 6 weeks/12 weeks/6 months, VAS leg score at 6 weeks/12 weeks/6 months/2 years and ODI at all postoperative time points (P < 0.045, all). In the VAS leg score >7 cohort, a greater proportion achieving MCID for VAS leg score at all postoperative time points and ODI at 12 weeks (P < 0.010, all). Postoperative satisfaction was greater in VAS back score ≤7 cohort for VAS leg score at 6 weeks/12 weeks/6 months/2 years, VAS back score at 12 weeks/2 years, and ODI at 6 weeks/12 weeks/6 months/2 years (P < 0.046, all). Patients with severe preoperative leg pain showed worse postoperative PROM scores and patient satisfaction for disability and back/leg pain. MCID achievement rates across cohorts were similar. Patients with severe leg pain may have expectations for surgical benefits incongruent with their postoperative outcomes, and physicians may seek to manage the preoperative expectations of their patients to reflect likely outcomes after MIS-TLIF.